Massive left ventricular pseudoaneurysm presenting as dysphagia: a case report. Issue 1 (3rd January 2023) - Pirzada, Ashar; Styles, Kim; Stewart, Robbie
Abstract: Background: Left ventricular pseudoaneurysm is a recognized, however, uncommon presentation of acute myocardial infarction in the current era. This is due to early reperfusion therapy for acute myocardial infarction. Left ventricular pseudoaneurysm after myocardial infarction can present in a variety of ways, including heart failure, chest pain, and dyspnoea. Case summary: We present a case of a 61-year-old male who presented with extremely atypical symptoms of dysphagia and weight loss due to a massive left ventricular pseudoaneurysm. Transthoracic echocardiogram and computed tomography revealed a large pseudoaneurysm causing mass effect on multiple gastrointestinal organs. Organic causes for dysphagia and weight loss were ruled out by gastroscopy. Surgical management was carried out but was ultimately unsuccessful. Discussion: Despite the heterogeneity in presentation for patients with left ventricular pseudoaneurysm, rapid diagnosis is important for management and prognosis. Diagnostic tools include transthoracic echocardiography, computed tomography, and cardiac magnetic resonance imaging. Management is usually surgical; however, there is some debate in the literature regarding conservative vs. surgical management for chronic pseudoaneurysms. More data are needed to determine optimal management strategies and prognosis for patients with left ventricular pseudoaneurysms.